Deletion of long noncoding RNA EFNA3 aggravates hypoxia‐induced injury in PC‐12 cells by upregulation of miR‐101a. Issue 1 (20th August 2018) - Gong, Weijun; Qie, Shuyan; Huang, Peiling; Xi, Jianing
Abstract: Long noncoding RNAs (lncRNAs) have been reported to be involved in several neurological pathogenesis conditions including cerebral ischemia. In the current study, the functions of lncRNA EFNA3 on hypoxia‐injured rat adrenal pheochromocytoma (PC‐12) cells and the underlying molecular mechanism were studied. The expression of lncRNA EFNA3 was silenced by short hairpin RNA transfection, after which the cells were subjected with hypoxia. Cell viability, migration, invasion, and apoptosis were, respectively, determined by trypan blue staining, Transwell assay, annexin V‐fluorescein isothiocyanate (FITC)/propidium iodide (PI) double‐staining, and Western blot analysis. The cross regulation between lncRNA EFNA3 and miR‐101a, as well as between miR‐101a and Rho associated coiled‐coil containing protein kinase 2 (ROCK2) were detected by performing quantitative real‐time polymerase chain reaction, RNA pull‐down, RNA immunoprecipitation, luciferase activity assay, and Western blot analysis. Studies showed that lncRNA EFNA3 was highly expressed in response to hypoxia. Deletion of lncRNA EFNA3 significantly aggravated hypoxia‐induced injury in PC‐12 cells, as the impairment of cell viability, migration, and invasion, and the inducement of apoptosis. LncRNA EFNA3 worked as a sponging molecule for miR‐101a and miR‐101a suppression‐protected PC‐12 cells against hypoxia‐induced injury even when lncRNA EFNA3 was silenced. ROCK2 was a target gene of miR‐101a. ROCK2 overexpression exhibited neuroprotective activities. Besides, ROCK2 overexpression activated Wnt/β‐catenin pathway whereas it deactivated JAK/STAT pathway upon hypoxia. Our study suggests that deletion of lncRNA EFNA3 aggravates hypoxia‐induced injury in PC‐12 cells by upregulating miR‐101a, which further targets ROCK2. Abstract : In this study, we explored the role of long noncoding RNA (lncRNA) EFNA3 in hypoxia‐injured PC‐12 cells, and tried to decode the possible underlying molecular mechanisms of lncRNA EFNA3's action in cerebral ischemia. This study will provide a better understanding of the pathogenesis of cerebral ischemia and may be helpful for the development of novel treatment strategies for cerebral ischemia‐induced stroke.